Eficiência da inoculação com diferentes estirpes de rizóbio em genótipos de feijão-caupi (Vigna unguiculata) em sistema agroecológico - Fernandes, Fernande Antunes (2012)
The experiments were conducted at the Fazenda Experimental de Iguatemi (FEI), Universidade Estadual de Maringá (UEM), in the area certified as organic, belonging to the Grupo de Agroecologia de Maringá (GAAMA). The objective of this study was the development of Vigna unguiculata cultivars when inoculated with different rhizobium strains in agroecological system. The cultivars used were Gurgueia (BR17) and Producer. The treatments consisted of seed inoculation with rhizobium strains UFLA 03-164, BR 3267, BR 3302 (UFLA 03-84), INPA 03-11b (BR3301) and UFLA 03-154 and three witnesses, with nitrogen (20 kg ha-1 N); without nitrogen fertilization and without inoculation; and without fertilization and without rhizobia , but with peat. The experimental design was a randomized block with four replications. There were no significant differences between any of the treatments Producer cultivar. In Gurgueia cultivating (BR17), only no was significant difference in mean dry mass of a nodule. By analyzing the Gurgueia cultivar, the two witnesses without nitrogen fertilization had similar performance to the witnesses with nitrogen. The Gurgueia cultivar inoculated with BR 3267 strain stood out negatively on productivity, as it showed significant difference when compared to the control without nitrogen and without peat.